Sustainable extended producer responsibility (EPR) model for managing household e-waste in Malaysia / Chow Ching Yan - Chow, Ching Yan (2017)
Household E-waste generation in Malaysia is estimated to increase 1% yearly. However, the collection, inventory, treatment and disposal practised at present are not optimum due to unavailability of a proper framework for Household E-waste Management. Therefore it is a known fact that Malaysia requires a sustainable and affordable system to manage E-waste. One option is to introduce Extended Producer responsibility (EPR) environmental policy, which focuses on shared responsibility by all the stakeholders. Hence, in this paper, four objectives were set up which are to determine the current status of Household E-waste Management in Malaysia, to compare Household E-waste Management systems in other countries from the EPR perspective (Germany, Japan, Taiwan, Malaysia), to identify the mechanism in implementing sustainable EPR model for managing Household E-waste in Malaysia and last but not least, the objective is to develop summaries sustainable EPR model for managing Household E-waste in Malaysia and overall recommendation. The methodologies adopted in order to complete this research are combination of literature review, non-participant observation method (attending a seminar), comparative analysis, flow diagram and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. EPR model practised in Germany, Japan and Taiwan are analysed in detail and assessed for suitability with or without modification for Malaysian scenario. It was found that even though there is variation in the ways that EPR is implemented in these countries, however, some main components are similar. Based on this finding, a total of seven components are identified for possible Malaysian EPR Model. The above mentioned components include regulation, Household E-waste inventory, collection, reporting, recycling, fee and Fund Management Board. In additions, a possible implementation plan complete with strengths, weakness, opportunities and threats is performed. The analysis confirms that EPR model for managing Household E-Waste is suitable in Malaysia.